2015
DOI: 10.1109/tuffc.2014.006601
|View full text |Cite
|
Sign up to set email alerts
|

Removal of residual nuclei following a cavitation event: a parametric study

Abstract: The efficacy of ultrasound therapies such as shock wave lithotripsy and histotripsy can be compromised by residual cavitation bubble nuclei that persist following the collapse of primary cavitation. In our previous work, we have developed a unique strategy for mitigating the effects of these residual bubbles using low amplitude ultrasound pulses to stimulate their aggregation and subsequent coalescence—effectively removing them from the field. Here, we further develop this bubble removal strategy through an in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 12 publications
(29 citation statements)
references
References 42 publications
0
29
0
Order By: Relevance
“…For example, increasing the treatment PRF has the potential to further shorten the treatment time under the same treatment dose if the cavitation memory effects can be reduced. Cavitation residual nuclei can be consolidated to reduce cavitation memory effects by interweaving low pressure ultrasound pulses with histotripsy pulses (Duryea et al 2015). Another possible investigation to further reduce cavitation memory effects would be to divide the treatment into more than two treatment passes.…”
Section: Discussionmentioning
confidence: 99%
“…For example, increasing the treatment PRF has the potential to further shorten the treatment time under the same treatment dose if the cavitation memory effects can be reduced. Cavitation residual nuclei can be consolidated to reduce cavitation memory effects by interweaving low pressure ultrasound pulses with histotripsy pulses (Duryea et al 2015). Another possible investigation to further reduce cavitation memory effects would be to divide the treatment into more than two treatment passes.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al (2012) showed that the number of pulses required to fractionate 25% of the target volume is reduced by more than an order of magnitude by increasing the time between pulses from 2 ms to >200 ms. Additionally, previous studies have employed an active acoustic technique termed bubble-removal to mitigate the cavitation memory effect. Duryea et al (2014, 2015a, 2015b) found that applying a low-amplitude ultrasound pulse with many cycles (~1000) following a cavitation event promoted the coalescence (by means of the secondary Bjerknes force) and aggregate translation (primary Bjerknes force) of residual nuclei from the focus.…”
Section: Introductionmentioning
confidence: 99%
“…Our recent work has aimed to develop a strategy for the active removal of residual bubble nuclei following a cavitation event [27, 28]. We have demonstrated that the application of appropriately designed low-amplitude ultrasound pulses can stimulate the aggregation and subsequent coalescence of a population of residual bubbles, effectively removing them from the field.…”
Section: Introductionmentioning
confidence: 99%
“…We have demonstrated that the application of appropriately designed low-amplitude ultrasound pulses can stimulate the aggregation and subsequent coalescence of a population of residual bubbles, effectively removing them from the field. These pulses—which we term bubble removal pulses—are typically on the order of one millisecond in duration and have maximal nuclei consolidation effects near a mechanical index (MI) of 1 [27, 28]. Previous work has also demonstrated that higher frequency bubble removal pulses (2 MHz) are more effective in comparison to lower frequency (500 kHz) for consolidation of the remnant cavitation nuclei that persist following histotripsy bubble cloud collapse [28].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation